Optimization of extraction process of jatropha oil by using quenching agent - Kothari, Richa; Ahmad, Shamshad; Samykano, M.; Tyagi, V. V.; Pandey, A. K.; Saidur, R. (IOP Publishing, 2021)
Among the various energy plant species, Jatropha curcus is found to be best oil-bearing plant species with a wide range of applications and having enormous economic potentials for its seed, which can be converted into biodiesel via transesterification which is an alternative to petrodiesel. In this present study, the effect of three factors, Time (1-4 hour), temperature (60-120°C) and quenching agents (NaCl, KCl, and ZrCl2) and dose of quenching agent(0.5-2gm) use for the extraction of oil from 10grm of jatropha seed. Using the Box-Benken Design (BBD) approach of Response Surface Methodology (RSM), 17 experimental runs were generated. n-Hexane was used as solvent for each experiment carried out in the 100 ml soxhlet extraction apparatus. Results obtained from the experiments were modeled and analyzed by choosing a quadratic model. From the analysis of modeled found temperature extraction time and dose of quenching agent revealed the good agreement of value (R2=0.98) between observed and predicted value of the experiment and were to be p>0.05 that was based on 95% confidence interval. By the use of RSM-BBD an optimizing experiment 60°C temperature 3h time and 2gm ZrCl2 quenching agent give best extraction of oil yield 41.41%.